2012
DOI: 10.1136/vr.100145
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the epidemiology of autumn nematodirosis in weaned lambs in a Scottish sheep flock

Abstract: Nematodirosis was diagnosed in the south-east of Scotland during two consecutive autumns in lambs which were grazed on the same field. The problem was unpredicted based on the knowledge of the pasture and animal management, and rudimentary understanding of the behaviour of free-living stages of Nematodirus battus in the region. Unlike the epidemiology that has been described in the south of England, whereby autumn infection of lambs is believed to arise from autumn hatching of eggs shed during the previous spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…Hatching in the absence of a chill has been previously documented, albeit at low levels, both historically [2,4,14] and more recently [6,7,15]. Previous studies of non-chilled hatching in N. battus highlighted variability between farm populations [3,7], consistent with the present findings.…”
Section: Discussionsupporting
confidence: 90%
“…Hatching in the absence of a chill has been previously documented, albeit at low levels, both historically [2,4,14] and more recently [6,7,15]. Previous studies of non-chilled hatching in N. battus highlighted variability between farm populations [3,7], consistent with the present findings.…”
Section: Discussionsupporting
confidence: 90%
“…The gastrointestinal nematodes (GIN), especially the species Haemonchus contortus, are highly prevalent parasites in small ruminants; also, they are responsible for large economic losses in livestock (Sargison et al, 2012). The GIN infections results in anemia, submandibular edema, weight loss, decrease in milk production, lethargy and increased death rate (Molento et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…While at first glance it would appear that there are a high number of holdings in NI where reduced drug efficacy is a problem, this may not in fact be the case. The five classes of anthelmintics claim efficacy against N. battus [ 55 ], although the parasite is a dose-limiting species for mebendazole (and other early, insoluble BZs) [ 27 ] and for most of the ML anthelmintics [ 37 ]. Reduced BZ activity was present in 35.7% of flocks tested with BZs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that up to ~70% of all deposited eggs will hatch without the chilling stimulus [ 19 ] and it has been suggested that the phenotypic plasticity in N. battus hatching behaviour represents a “bet-hedging” strategy that allows the establishment of “chilled” larvae in parasite-naïve lambs, supplemented by infection later in the season by larvae produced from “non-chilled” eggs [ 20 ]. In recent years, increasingly, outbreaks of nematodirosis have been seen later in the grazing season (or indeed in the Autumn) in older lambs [ 20 27 ]. This has already been reported for NI [ 4 ].…”
Section: Introductionmentioning
confidence: 99%